Concussion reporting and perceived knowledge of professional fighters. Issue 3 (3rd July 2019) - Bennett, Lauren L.; Arias, Jalayne J.; Ford, Paul J.; Bernick, Charles; Banks, Sarah J.
ABSTRACT: Objective : For concussions to be effectively managed in sports, they need to be correctly identified and reported. The extent to which professional athletes correctly recognize concussions, and their willingness to report symptoms, is not yet well understood. Given the risk of head injuries leading to concussions across combat sports, insight into professional fighters' knowledge and reporting of concussive symptoms is essential to improve concussion management. Methods : To investigate understanding and reporting patterns of concussions sustained while training or competing, 257 fighters completed a self-report questionnaire assessing self-perception of concussion knowledge, trust of ringside medical providers, and reported number of previous head injuries. Fighting history, including number of knockouts, was obtained from self-report (amateur) and published (professional) records. Results : Significant gaps in fighters' perceived knowledge of concussion symptoms and long-term effects of multiple concussions emerged. Approximately 40% of fighters reported returning to training or competition the same day a head injury was sustained, while 21% of fighters endorsed concealing symptoms of head injury from medical providers and coaches. Conclusions : Confusion surrounding terms used to describe head injuries amongst fighters (e.g., concussions, knockouts), coupled with limited understanding of concussive symptoms and a desire to return to competition, likely contributes to significant underreporting of symptoms.